Image analysis reveals differences in tumor multinucleations in Black and White patients with human papillomavirus‐associated oropharyngeal squamous cell carcinoma. Issue 21 (6th September 2022) - Koyuncu, Can F.; Nag, Reetoja; Lu, Cheng; Corredor, Germán; Viswanathan, Vidya S.; Sandulache, Vlad C.; Fu, Pingfu; Yang, Kailin; Pan, Quintin; Zhang, Zelin; Xu, Jun; Chute, Deborah J.; et al.
Abstract : Background: Understanding biological differences between different racial groups of human papillomavirus (HPV)‐associated oropharyngeal squamous cell carcinoma (OPSCC) patients, who have differences in terms of incidence, survival, and tumor morphology, can facilitate accurate prognostic biomarkers, which can help develop personalized treatment strategies. Methods: This study evaluated whether there were morphologic differences between HPV‐associated tumors from Black and White patients in terms of multinucleation index (MuNI), an image analysis‐derived metric that measures density of multinucleated tumor cells within epithelial regions on hematoxylin–eosin images and previously has been prognostic in HPV‐associated OPSCC patients. In this study, the authors specifically evaluated whether the same MuNI cutoff that was prognostic of overall survival (OS) and disease‐free survival in their previous study, TTR, is valid for Black and White patients, separately. We also evaluated population‐specific cutoffs, TB for Blacks and TW for Whites, for risk stratification. Results: MuNI was statistically significantly different between Black (mean, 3.88e–4; median, 3.67e–04) and White patients (mean, 3.36e–04; median, 2.99e–04), with p  = .0078. Using TTR, MuNI was prognostic of OS in the entire population with hazard ratio (HR) of 1.71 ( p  = .002; 95% confidence interval [CI], 1.21–2.43) and in White patients with HR of 1.72 ( p  = .005; 95% CI, 1.18–2.51). Population‐specific cutoff, TW, yielded improved HR of 1.77 ( p  = .003; 95% CI, 1.21–2.58) for White patients, whereas TB did not improve risk‐stratification in Black patients with HR of 0.6 ( p  = .3; HR, 0.6; 95% CI, 0.2–1.80). Conclusions: Histological difference between White and Black patient tumors in terms of multinucleated tumor cells suggests the need for considering population‐specific prognostic biomarkers for personalized risk stratification strategies for HPV‐associated OPSCC patients. Abstract : There are substantial differences between different racial groups of human papillomavirus‐related oropharyngeal squamous cell carcinoma (OPSCC) patients, in terms of survival and tumor morphology. In this study, the authors demonstrated a histological difference between tumors from White and Black OPSCC patients using a computational pathology‐based metric called the multinucleation index.